Management of Trigeminal Neuralgia with Homoeopathy in Patient with the Extracted Teeth: A Case Report (Homoeopathy for All, 2025)
This is a case report of management of Trigeminal neuralgia esp. after teeth extraction. A majority of patients who sustain injuries to the peripheral sensory nerves of the face and jaws experience a slow but gradual return of sensation that is functional and tolerable, if not the same as before the injuries. In some of these patients, posttraumatic symptoms become pathological and are painful. These symptoms can significantly affect the patient's quality of life. In this case, the patient developed trigeminal neuralgia following dental extraction, leading to severe, debilitating pain. The report outlines the treatment approach employed, highlighting the use of appropriate interventions of homoeopathic medicine to manage the pain and prevent further complications.
Keywords: Trigeminal neuralgia; teeth extraction; homoeopathy